The identification of osmoprotectant compounds from Jatropha curcas Linn. plant for natural drought stress tolerance. (February 2020) - Winaya, Aris; Maftuchah,; Zainudin, Agus
Abstract: One of the plant species that its seed can produce oil for biodiesel material is Jatropha curcas Linn. The using of J. curcas plant for supporting the conversion of fossil fuel to biofuel and the utilization for dry land in Indonesia is very prospective. However, it is necessary to create J. curcas varieties that are tolerant to drought stress. The objective of this study was to identify the content of osmoprotectant compounds in J. curcas as a natural tolerance to drought stress. The plants sampled were six weeks old by isolation of the sap from plant stems and then followed by Gas Chromatography–Mass Spectrometry (GC–MS) analysis. This study was found to be suspected of 15 osmoprotectant compounds in the sap of J.curcas namely glycine, serine, proline, valine, threonine, leucine, asparagine, salicylic acid, glutamine, methionine, phenylalanine, arginine, tyrosine, raffinose, and stachyose. The three main of osmoprotectant compounds were suspected as stachyose (8.40%), raffinose (6.78%) and leucine (2.64%), while the low level of osmoprotectant included salicylic acid (0.16%), and followed by lycine, serine and methionine with the similar content (0.24%). It is therefore, in the future J. curcas can potentially be utilized for dry land reforestation and biofuel production.